Evaluación del promotor de crecimiento hematofos b 12 administrado vía oral en Pollos de engorde en la ciudad de Babahoyo. - Rivera Zambrano, Roberto Antonio (2012)
The present investigation work was carried out in the city of Babahoyo, in the Experimental Farm San Pablo of the School Veterinary Medicine and Zootecnia of the Ability of Agricultural Sciences that it is located in the km 7 1/2 of the road to Montalvo of The Ríos' County, with a temperature average of 25.2°C, located to 8 msnm. Whose geographical localization is 1°46" of south latitude and 97° 27" of latitude west and a precipitation I average yearly of 1800 mm. It had a duration of 42 days and they were used a total of 250 chickens broilers of the line Ross, distributed in five groups of the same age and each one has 50 chickens, which made the times of parcel of treatment witness (To) and parcel of experimental treatment respectively. (T1), (T2), (T3) AND (T4). The purpose of the investigation proposal was to evaluate the promoter's of growth effect Hematofos B 12 administered via oral in chickens of it puts on weight in the city of Babahoyo, they were carried out all the sanitary, biological works and of 53 feeding daily, without novelties of importance in what concerns to serious problems or non solucionables in a period of time that you/they interfere in the final result of the investigation. I take the pesos weekly and they registered the securities of food consumption daily, consumption of water, mortality and overturned securities (costs of production), the data were evaluated totally at random by means of the design that I determine us that there was high statistical significancia (P£0,05), the accumulated nutritious conversion of the group T4 (1.96) it was the best, the percentage of mortality it was of 4% for the groups T1 and T2 while for the other groups it was of 0%, the analysis économico determined that the group T 3 obtained a bigger utility with relationship to the other treatments, the relationship cost benefit determined that ecónomicamente is not advisable the use of the Hematofos B 12 oral as promoter of growth in chickens of it puts on weight.